Theranostic mercury: 197(m)Hg with high specific activity for imaging and therapy. (March 2015) - Walther, Martin; Preusche, Stephan; Bartel, Stig; Wunderlich, Gerd; Freudenberg, Robert; Steinbach, Jörg; Pietzsch, Hans-Jürgen
Abstract: The no carrier added (NCA) radionuclide 197(m) Hg is accessible through proton induced nuclear reactions on gold. The decay properties of both simultaneous produced nuclear isomers 197m Hg and 197 Hg like convenient half life, low energy gamma radiations for imaging, Auger and conversion electrons for therapy are combined with unique chemical and physical properties of mercury and its compounds. Gold as a monoisotopic element has a natural abundance of 100% 197 Au superseding expensive enrichment for the target material. Additionally, the high thermal conductivity of gold enables high beam current irradiations. For separation of target material a liquid–liquid extraction method was applied. Highlights: No carrier added 197(m) Hg. 197(m) Hg promising for therapeutic application. 197(m) Hg for imaging.